Effects of Oil Palm Plantations on the Habitat Structure and Biota of Streams in Eastern Amazon. (16th June 2016) - Juen, L.; Cunha, E. J.; Carvalho, F. G.; Ferreira, M. C.; Begot, T. O.; Andrade, A. L.; Shimano, Y.; Leão, H.; Pompeu, P. S.; Montag, L. F. A.
Abstract: Oil palm plantations have expanded around the world, increasing concern about its pressure on deforestation rates and the homogenization of the landscape. In this context, the present study aimed to evaluate the impact of oil palm plantations on the physical characteristics of streams in Amazonia and their effects on Heteroptera, Odonata and Fish assemblages. A total of 23 streams were sampled, eight within fragments of primary forest, while 15 were in oil palm plantations. Data were collected on characteristics of the channel morphology, substrate, hydraulics, instream cover for aquatic organisms, riparian vegetation, human impacts and woody debris. Instream cover and proximity of human impacts were the variables that had the greatest effects on the physical structure of the streams, showing variation between streams of forest in pristine areas and oil palm plantations. Of the analyzed parameters, substrate, instream cover and woody debris influence the richness of Heteroptera, Odonata and Fish. The impact of oil palm plantations on local streams depended on the size of the plantations, and they cannot be considered an adequate substitute for lost habitats in efforts to preserve the physical habitat of Amazonian streams. Any type of conversion of the natural forest can have direct or indirect impacts on the dynamics and structure of these environments, with potentially negative consequences for their biodiversity. The maintenance of an adequate buffer zone of native riparian vegetation adjacent to the streams that flow through the plantations recommended, because this appears to be the principal factor determining the physical conditions of these streams. Copyright © 2016 John Wiley & Sons, Ltd.